'Accepting where I'm at' – a qualitative study of the mechanisms, benefits, and impact of a behavioral memory intervention for community-dwelling older adults. (2nd September 2017) - Vandermorris, Susan; Davidson, Sylvia; Au, April; Sue, Joanna; Fallah, Shafagh; Troyer, Angela K.
ABSTRACT: Objective : Gain novel, in-depth insight into therapeutic mechanisms, benefits, and impact of a multi-modal behavioral memory intervention for older adults with concerns about memory. Methods : Participants were11 community-dwelling older adults (aged 63–88) who completed the Memory and Aging Program, an evidence-based multi-modal group intervention for normal age-related memory change. Semi-structured interviews were administered post-intervention. Responses were analyzed using qualitative content analysis until meaningful themes were agreed upon. Results : Analyses revealed a main theme of normalization as the overarching benefit of participation. The mechanism for this comprised both specific intervention content and the process of participating with others. A positive impact of the intervention was demonstrated at emotional (feelings of reassurance, hope, and confidence) and functional (increasing motivation for lifestyle change) levels; for some, there was a direct link between emotion and function. Conclusion : This study highlighted a single, prominent therapeutic benefit of normalization, illustrated a dual mechanism for achieving this, and characterized a nuanced inter-relationship of the emotional and functional impact of the intervention for participants. Results support the notion that group behavioral interventions can educate, empower, and promote psychological well-being in older adults and may be an effective avenue to reduce risk of disease and promote sustained functional independence.